Injection molding of a starch/EVOH blend aimed as an alternative biomaterial for temporary applications - Sousa, R. A. (2000)
Biodegradable polymers show great potential to be used as materials for temporary implants and bone replacement applications in orthopedics. However, its use in high load-bearing applications will depend on the successful development of biodegradable implants with a mechanical performance matching that of human bone. This article describes the optimization of the injection molding process of an alternative biodegradable starch-based polymer aimed at biomedical applications. A blend of starch with a copolymer of ethylene-vinyl alcohol (SEVA-C) was studied. Both conventional injection molding and shear controlled orientation (SCORIM) were optimized with the support of design of experiments and analysis of variance techniques. The mechanical characterization was performed by tensile testing. The structure developed within the moldings was assessed by wide-angle X-ray diffraction and differential scanning calorimetry. Increases up to 30% in the tangent modulus and 20% in the ultimate tensile strength compared with conventional molding were achieved with the application of SCORIM. The holding pressure and the frequency of the shear applied have the strongest influence on the morphology development and consequently on the mechanical performance. The solidification of SEVA-C at high cavity pressures enhances stiffness for long durations of the shearing stage in SCORIM. However, the effect of viscous heating of SEVA-C is important and ought to be considered. A decrease of the material phase miscibility in SEVA-C occurs as result of the shear fields imposed. The microstructure evaluation suggests that the mechanical properties enhancement in SCORIM molded SEVA-C is attributable to preferred orientation developed during processing